Flexible and Transferable Silver Nanowire Liquid Crystal Polymer Film Obtained via Photo‐Alignment Programming. Issue 16 (1st July 2022) - Sang, Jingxin; Zhang, Juan; Feng, Hange; Sun, Jiatong; Shang, Jianhua; Zhang, Yihong; Zhao, Shuguang; Neyts, Kristiaan; Chigrinov, Vladimir
Abstract: The self‐assembly of silver nanowires (AgNWs) with a high aspect ratio is highly desirable for practical applications; however, several challenges still exist. Herein, a non‐contact, simple, large‐scale, micro‐domain photo‐alignment technology is proposed to align AgNWs in a liquid crystal polymer (LCP) film, resulting in a high order parameter (above 0.9). The AgNWs are precisely controlled to have planar alignment and twisted nematic structures in micro‐multi‐domains. The AgNW/LCP precursor is frozen to shape the film via ultraviolet crosslinking, allowing it to be easily peeled off and transferred to various flexible and other functional substrates. The aligned AgNWs can be used to improve the mechanical properties of LCP films, as they exhibit high elongation‐at‐break and high strength‐at‐break. The AgNW/LCP film can also be further programmed by micro‐multi‐domain photo‐alignment for use in flexible and wearable devices. Abstract : A non‐contact photo‐alignment technology is proposed to align silver nanowires (AgNWs) in a liquid crystal polymer (LCP) film with high‐order parameter. They are controlled to have planar alignment and twisted nematic structures in micro‐multi‐domains. The aligned AgNWs can be used to improve the mechanical properties of LCP films. The AgNW/LCP film can be programmed by micro‐multi‐domain photo‐alignment for use in flexible and wearable devices.